Usefulness of the Jump-and-Reach Test in assessment of vertical jump performance - Menzel, H-J.; Chagas, M. H.; Szmuchrowski, L. A.; Araujo, S. R.; Campos, C. E.; Giannetti, M. R. (Perceptual and Motor Skills, 2010)
The objective was to estimate the reliability and criterion-related validity of the Jump-and-Reach Test for the assessment of squat, countermovement, and drop jump performance of 32 male Brazilian professional volleyball players. Performance of squat, countermovement, and drop jumps with different dropping heights was assessed on the Jump-and-Reach Test and the measurement of flight time, then compared across different jump trials. The very high reliability coefficients of both assessment methods and the lower correlation coefficients between scores on the assessments indicate a very high consistency of each method but only moderate covariation, which means that they measure partly different items. As a consequence, the Jump-and-Reach Test has good ecological validity in situations when reaching height during the flight phase is critical for performance (e.g., basketball and volleyball) but only limited accuracy for the assessment of vertical impulse production with different jump techniques and conditions.